Analisis Kebijakan Tata Ruang Indonesia Dan Belanda - Maldino, Teuku Fito Agus; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
This study aimed to compared the spatial policy between Indonesia and Netherlands. In which caused by the spatial arranging in Indonesia that still raises a few different issues, such as the transformation of agrarian arrive, the increasement of recurrence and scope of catastrophes, ghetto lodging and natural pullution, so the beliefs of the Indonesian individuals to form a fair and affluent society are troublesome to be realized. This study used the normative juridical method as a research method, where the data is obtained from literature studies using secondary data. The data obtained were compared and analyzed descriptively. The comes about appeared that the government must quickly recreate Law No. 26 of 2007 with respect to Spatial Planning because it is no longer in accordance with the current conditions. Subsequently, the government also needs to establish permanent and independentinstitutions to coordinate spatial planning policy at the central and regional levels. In addition, it is necessary to increase community participation in managing spatial planing policy aimed at fostering awareness and compliance with spatial planning policy